The Anthropologist (AND) The Theologian - Chino, Taido (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2017)
This article is an attempt to determine the grounds for an interdisciplinary conversation between anthropology and theology. The first section reflects on Ludwig Feuerbach’s infamous assertion that theology is no more than anthropology and the obstacle that presents for fruitful dialogue. The second section considers the writings of a contemporary social anthropologist and theologian, Eduardo Viveiros de Castro and Christoph Schwöbel, respectively, with the aim of identifying intellectual resources from within each discipline which would recommend a mutually beneficial exchange. In particular, attention is given to the distinct ways each develops a metaphysics of relationality that overcomes difficulties within their own fields of study. Building on their similar relational conceptual frameworks, the primary contribution this essay makes is to extend their thought to the question of interdisciplinary conversation itself by suggesting that a dialogue is possible and, in fact, necessary. The article concludes with a third section that revisits the Feuerbachian critique and responds with a brief consideration of the relationship between divine and created being.